Development and Validity and Reliability Tests of Professionalism Assessment Instrument in Psychiatry Residents - Budi Santoso; Carla Raymondalexas Marchira; P. Sumarni (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: The main objective of specialist training program is professionalism and competence. In modern era, the medical professions have to face legal issues. This problem can be overcome by improving professionalism education and routine evaluation of professionalism during specialist training. Psychiatric specialist training in particular is different from other specialist training due to several unique aspects during the course of the training. Therefore, an instrument to assess professionalism of psychiatric residents is required. The objective of this study was to develop an instrument to assess professionalism for psychiatric residents adapted from ACGME (Accreditation Council for Graduate Medical Education).Method: This study was a quantitative non-experimental study consisted of 3 stages (literature review, peer review, and validity and reliability testing). The subjects were residents on training at the Department of Psychiatry, Medical Faculty, Gadjah Mada University. The construct validity testing was conducted with Confimatory Factor Analysis (CFA) and content validity with Pearson’s product moment. Reliability testing was conducted with Cronbach’s alpha. Results: Statistical analyses results showed that instrument was valid (Pearson’s product moment r = 0.302 – 0.797; p = 0.001 – 0.052) and reliable (Cronbach’s alpha = 0.943). Analyses on the subjects score revealed that professionalism was associated with the stage of training. The t-test results showed that subjects in the post-stasis stage showed higher professionalism score except for the 4th domain (professional behavior).Conclusion: The instrument that developed was valid and reliable to be use as a mean to assess professionalism for resident in training at the Department of Psychiatry, Medical Faculty, Gadjah Mada University.